CIPRE TAKES UP THE CHALLENGE - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
Jean-Blaise Kenmogne, Cercle International pour la Promotion de la Creation, Bafoussam, Cameroon: 'Following the articlewhich was published in Spore 62 (French version) and Spore 63 (English version) on compost making, many people havewritten...